Benefits and Risks of Aliskiren Treatment in Patients With Type 2 Diabetes: Analyses of the 3A Registry. Issue 10 (20th April 2016) - Kistner, Iris; Zeymer, Uwe; Dechend, Ralf; Hagedorn, Ina; Riemer, Thomas; Bramlage, Peter; Pittrow, David; Senges, Jochen; Schmieder, Roland E.
Abstract : The authors sought to retrospectively analyze the real‐world evidence on aliskiren in diabetic patients with or without concomitant renin‐angiotensin system (RAS) blocker use based on the Registry for Ambulant Therapy With RAS Inhibitors in Hypertension Patients in Germany (3A). Of 14, 986 patients included, 3772 patients had diabetes and 28.5% received aliskiren, 14.3% received angiotensin‐converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARBs), 35.4% received aliskiren plus an ACE inhibitor/ARB, and 10.5% received other drugs. Ambulatory blood pressure (BP) monitoring (baseline BP 148±15.8/84.0±10.9 mm Hg) revealed stronger diastolic BP reduction for aliskiren plus ACE inhibitor/ARB than aliskiren alone in the low (2.8±0.5 vs 0.6±0.6; P =.004) and intermediate (5.9±0.5 vs 4.5±0.5; P =.04) baseline BP groups. There was a lesser ambulatory BP reduction observed for patients receiving non‐RAS in the high baseline category for both systolic (12.5±1.8 vs 17.1±1.0; P =.02) and diastolic (6.9±1.0 vs 9.8±0.6; P =.01) BP. In patients with hypertension and type 2 diabetes, aliskiren was beneficial in lowering BP, with no observed increases in major adverse effects compared with RAS‐blocking therapy alone.